A multimodal biomechanical and eye-tracking dataset of suprapostural coordination in healthy young adults - Madhur Mangalam; Mahsa Barfi; Theodore Deligiannis; Brian Schlattmann (Scientific Data)
Abstract We present a publicly available dataset, offering annotated full-body kinematics, gaze tracking, and ground reaction forces and moments from 48 healthy young adults performing a life-size suprapostural task. Using a 12-camera motion capture system, eye tracker, and force plate, we recorded full-body kinematics, eye gaze and pupil diameter, and ground reaction forces and moments as participants completed four tasks: standing upright, performing the Trail Making Test (TMT) Part A projected on a screen using a laser pointer and repeating these conditions on a wobble board inducing instability along the mediolateral axis. Each trial lasted five minutes, and the total number of trail connections was recorded. The dataset comprises raw and processed data on TMT trajectories, individual performance scores, video recordings of the TMT, full-body kinematics, the center of mass (CoM), joint angles, eye gaze and pupil diameter, ground reaction forces and moments, and the center of pressure (CoP). This resource provides an unprecedented opportunity to investigate balance, motor control, and cognitive performance during concurrent suprapostural tasks.